Discovering the Potentials of Four Phage Endolysins to Combat Gram-Negative Infections - Vasina, Daria V.; Antonova, Nataliia P.; Grigoriev, Igor V.; Yakimakha, Victoria S.; Lendel, Anastasiya M.; Nikiforova, Maria A.; Pochtovyi, Andrei A.; Remizov, Timofey A.; Usachev, Evgeny V.; Shevlyagina, Natalia V.; Zhukhovitsky, Vladimir G.; Fursov, Mikhail V.; et al. (Frontiers in Microbiology, 2021)
Endolysin-based therapeutics are promising antibacterial agents and can successfully supplement the existing antibacterial drugs array. It is specifically important in the case of gram-negative pathogens, e.g., ESKAPE group bacteria, which includes Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter species and are highly inclined to gain multiple antibiotic resistance. Despite numerous works devoted to the screening of new lytic enzymes and investigations of their biochemical properties, there are significant breaches in some aspects of their operating characteristics, including safety issues of endolysins use. Here we provide a comprehensive study of antimicrobial efficacy aspects of four gram-negative bacteria-targeting endolysins LysAm24, LysAp22, LysECD7 and LysSi3, their in vitro and in vivo activity and biological safety. These endolysins possess a wide spectrum of action, are active against planktonic bacteria and bacterial biofilms and effective in wound and burn skin infection animal models. In terms of safety, these enzymes do not contribute to the development of short-term resistance, are not cytotoxic and do not significantly affect the normal intestinal microflora in vivo. Our results provide a confident base for the development of effective and safe candidate dosage forms for the treatment of local and systemic infections caused by gram-negative bacterial species.